The Role of Municipal Energy Companies in Sustainable Local Energy Systems - Bauer, Fredric (My University, 2012)
When constructing sustainable energy systems the local level of implementation is very important, and yet sometimes neglected. This thesis focuses on the local implementation of Swedish policy for energy and environment. Municipally owned energy companies have a large responsibility in developing sustainable local energy systems as their business lies between local policy, described in the municipal energy plans, and the competitive energy markets for electricity and heat. The thesis investigates the role of policy, national and local, and how the policy governs the environmental efforts of the municipal energy companies, related to the national environmental quality objectives. A case study of three municipalities in the western part of Sweden shows that the companies are often important actors when developing the municipal energy plan and that the companies have a large degree of freedom when planning future investments. The directives from the owners, the municipalities, are often vague and only sometimes use clearly defined indicators to evaluate the development of the local energy system and its environmental impact. Business areas in which the companies have had great success include district heating which often has achieved a large share of the heat market, whereas wind power seems to be a difficult issue for the companies to engage, even though the companies generally seem to have a large acceptance for their activities locally. Energy plans could further stress the need for evaluation of investments and system development using properly defined indicators, which can easily be adopted from the national indicators in the environmental quality objective system.
Keywords: Energi; Grundläggande vetenskaper; Materialteknik; Energy; Basic Sciences; Materials Engineering